Employment situation in people with Long COVID: Analysis of associated sociodemographic and clinical factors. - León-Herrera, Sandra; Samper-Pardo, Mario; Asensio-Martínez, Angela (Acciones e Investigaciones Sociales, 2023)
Introduction: The characteristic symptomatology of Long-COVID syndrome affects the physical and cognitive functioning of people who suffer from it, creating challenges when returning to their usual job. The objective of this study was to deepen the understanding of the employment status of people with this syndrome and its associated sociodemographic and clinical factors. Material and methods: A cross-sectional study was carried out with the participation of 83 patients diagnosed with Long-COVID, over 18 years of age and attended by Primary Health Care in the Autonomous Community of Aragon. The main study variable was the employment status of the participants, in addition to collecting sociodemographic and clinical data through a structured interview. Subsequently, a descriptive, correlation and regression statistical analysis was performed using the SPSS Statistics program. Results: Of the 83 study participants, 55.4% were in an active employment situation, and 44.6% in a situation of temporary incapacity for work. A greater number of persistent symptoms and belonging to the male gender were predictors of a greater probability of being in a situation of temporary incapacity for work. Discussion: A large percentage of people with Long-COVID are on sick leave or temporary incapacity for work, which makes it necessary to develop prevention and action programs from socio-health care teams with the aim of these people not losing their jobs temporarily or permanently or, if this has already happened, return to their previous work situation as soon as possible.